Targeting the Synapse in Alzheimer’s Disease - Jackson, Johanna; Jambrina, Enrique; Li, Jennifer; Marston, Hugh; Menzies, Fiona; Phillips, Keith; Gilmour, Gary (Frontiers in Neuroscience, 2019)
Dynamic gain and loss of synapses is fundamental to healthy brain function. While Alzheimer’s Disease (AD) treatment strategies have largely focussed on beta-amyloid and tau protein pathologies, the synapse itself may also be a critical endpoint to consider regarding disease modification. Disruption of mechanisms of neuronal plasticity, eventually resulting in a net loss of synapses, is implicated as an early pathological event in AD. Synaptic dysfunction therefore may be a final common biological mechanism linking protein pathologies to disease symptoms. This review summarises evidence supporting the idea of early neuroplastic deficits being prevalent in AD. Changes in synaptic density can occur before overt neurodegeneration and should not be considered to uniformly decrease over the course of the disease. Instead, synaptic levels are influenced by an interplay between processes of degeneration and atrophy, and those of maintenance and compensation at regional and network levels. How these neuroplastic changes are driven by amyloid and tau pathology are varied. A mixture of direct effects of amyloid and tau on synaptic integrity, as well as indirect effects on processes such as inflammation and neuronal energetics are likely to be at play here. Focussing on the synapse and mechanisms of neuroplasticity as therapeutic opportunities in AD raises some important conceptual and strategic issues regarding translational research, and how preclinical research can inform clinical studies. Nevertheless, substrates of neuroplasticity represent an emerging complementary class of drug target that would aim to normalise synapse dynamics and restore cognitive function in the AD brain.